MicroRNA‐200c overexpression in cancer‐associated fibroblasts reduces the invasive properties of breast tumour cells. Issue 3 (15th September 2022) - Shenavar, Nasim; Shariati, Laleh; Hakimian, Mohammad Reza; Makvandi, Pooyan; Javanmard, Shaghayegh Haghjooy
Abstract: Cancer‐associated fibroblasts (CAFs) play a critical role in supporting tumour cells in all aspects of cancer development, such as cell proliferation, migration and angiogenesis. MicroRNAs (miRNAs) as regulatory molecules regulate the genes contributing to cell growth, differentiation, migration and apoptosis. According to the literature, miR‐200c, as a tumour suppressor, has low expression levels in CAFs. In this investigation, the effect of miR‐200c overexpression was evaluated on proliferation, migration and angiogenesis of triple‐negative breast cancer (TNBC) cells. The fibroblasts were isolated from normal and cancerous breast tissue. MiR‐200c expression was assessed using real‐time polymerase chain reaction in cancer‐associated and normal fibroblasts. Then, the effect of miR‐200c transfection on proliferation, migration and angiogenesis of TNBC cells was evaluated. Our results confirm that in the presence of miR‐200c transfected fibroblasts, the proliferation, migration and angiogenesis of cancer cells significantly decreased. This effect could be attributed to the reduction of growth factors provided by cancer‐associated fibroblasts after miRNA dysregulation. These results propose that miR‐200c acts as an effective tumour suppressor in many aspects of TNBC development and can be considered a potential therapeutic tool for breast cancer in the next generation of pharmaceutics. Abstract : Graphical Headlights Cancer‐associated fibroblasts (CAFs) play a great role in breast cancer progression. MicroRNAs (miRNAs) play an important role in the transformation of normal fibroblasts to CAF. miRNA‐200c overexpression decreases the invasive features of cancer cells.